Adaptation of Historical Figures into Mobile Game Characters (Case Study: Hijikata Toshizo from Fate/Grand Order) - Iqbal Baihaqi; Hafiz Aziz Ahmad; Dana Waskita (Bina Nusantara University, 2022)
Movies and animations widely liked usually have good character designs. The audience often encounters elevating historical figures as one of the characters in the designed media, so it is necessary to understand what things need to be present when visualizing these characters. Hijikata Toshizo in history is a famous samurai in Japan and is a historical figure and often appointed in entertainment media such as animation, games, and comics, so Hijikata Toshizo is very popular among lovers of Japanese culture and history. The visual changes from the Hijikata Toshizo character in Japanese history to the Hijikata Toshizo character in Fate/Grand Order are analyzed so that it can be an additional reference for designers when designing characters based on historical figures. After the related data was collected, the data was later analyzed with the Manga-matrix method introduced by Hiroyoshi Tsukamoto to analyze the character design's shape, costume, and personality. According to the results of the analysis, there are similarities and variances in the character of the Hijikata Toshizo game and its historical counterpart. Each element was brought about through the use of historical evidence and the designer's creativity.